2023
DOI: 10.4143/crt.2021.1514
|View full text |Cite
|
Sign up to set email alerts
|

Suggestions for Escaping the Dark Ages for Pediatric Diffuse Intrinsic Pontine Glioma Treated with Radiotherapy: Analysis of Prognostic Factors from the National Multicenter Study

Abstract: This multicenter retrospective study aimed to investigate clinical, radiologic, and treatmentrelated factors affecting survival in patients with newly diagnosed diffuse intrinsic pontine glioma (DIPG) treated with radiotherapy. Materials and MethodsPatients aged <30 years who underwent radiotherapy as an initial treatment for DIPG between 2000 and 2018 were included; patients who did not undergo magnetic resonance imaging at diagnosis and those with pathologically diagnosed grade I glioma were excluded. We exa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…In this 10-year single-center study, we evaluated the survival outcomes, as well as the clinical, radiological, and therapeutic response-related factors that affect prognosis, in children with DIPG who received radiation therapy. Our findings confirmed some previously reported survival-related factors in DIPG patients [ 11 , 12 , 14 , 17 , 21 ], such as extrapontine lesion extension, necrosis, ring enhancement, Karnofsky, therapeutic response, and increased ring enhancement post-radiotherapy. Our results showed that 39% of patients exhibited ring enhancement, which is generally the same as previously reported results, and the proportion of patients with ring enhancement was approximately 35–37% [ 11 , 12 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this 10-year single-center study, we evaluated the survival outcomes, as well as the clinical, radiological, and therapeutic response-related factors that affect prognosis, in children with DIPG who received radiation therapy. Our findings confirmed some previously reported survival-related factors in DIPG patients [ 11 , 12 , 14 , 17 , 21 ], such as extrapontine lesion extension, necrosis, ring enhancement, Karnofsky, therapeutic response, and increased ring enhancement post-radiotherapy. Our results showed that 39% of patients exhibited ring enhancement, which is generally the same as previously reported results, and the proportion of patients with ring enhancement was approximately 35–37% [ 11 , 12 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Age ≤3 or >10 years and longer symptom duration at presentation are prognostic factors associated with a favorable survival outcome [ 8 15 ]. A Korean study [ 10 ] also confirmed these significant prognostic factors.…”
Section: Radiotherapy As a Definitive Treatmentmentioning
confidence: 71%
“…Similar to the current recommendation, the Children’s Cancer Study Group study performed in 1977 recommended radiotherapy to be administered 5 times a week at 8–9 Gy/week up to 50–60 Gy [ 9 ]. A Korean Radiation Oncology Group (KROG) study reported that the radiotherapy dose did not change over the last 20 years in clinical practice in Korea, and most patients received 54 Gy of radiation with conventional fractionation [ 10 ].…”
Section: Radiotherapy As a Definitive Treatmentmentioning
confidence: 99%
See 2 more Smart Citations